Compressive strength and crack propagation of cement composites reinforced coconut fibre - Alida, Abdullah; Shamsul Baharin, Jamaludin, Prof. Dr.; Mazlee, Mohd Noor; Kamarudin, Hussin, Brig. Jen. Dato' Prof. Dr. (Medwell Journals, 2013)
link to publisher's homepage at www.medwelljournals.org/